“La cara de luna de mi madre”: Nuria Amat’s Revolution in Poetic Language in “Casa de verano” (1999) - David Richter (Studies in 20th & 21st Century Literature, 2013)
Nuria Amat’s 1999 short story “Casa de verano” ‘Summer House’ presents the reader with a sensorial collage of unsettling language and violent images that effectively portray domestic abuse and the difficulty of escaping oppressive environments. The Barcelona writer’s text crosses the generic boundaries of narrative and poetry as her discourse flows freely and irrationally by employing a wide variety of charged poetic devices such as metaphor, metonymy, and antithesis. The story focuses on three orphan children who are prohibited from speaking about their subversive bisexual mother, from reading the few remaining books in the summer house, or from playing with most of their toys. They cope with the rigid house rules by seeking refuge in their imagination and escaping to a world of lyrically-encoded language. The children’s linguistic nonsense is comprised mostly of dislocated phrases which contest the dictates of their Franco-like abuelo ‘grandfather’ as they speak metaphorical utterances and “desordenando palabras” ‘muddling up words.’ These speech acts disrupt generic conventions and issue a revolutionary aesthetics similar to what Julia Kristeva refers to as the semiotic chora, (pre)linguistic mobilizations that are in direct contrast to the official regulations of the symbolic order. Their dreams of escaping the summer house are heard through fragmented memories, maternal metaphors, and a feminist politics wherein unstable notions of both gender identity and genre challenge traditional discourses. As such, Amat’s “Casa de verano” constitutes a daring poetic narrative centered on youthful resistance and feminine dissidence.
Keywords: Nuri Amat; Casa de verano; domestic abuse; violence; oppression; poetry; poetic narrative; imagination; (pre)linguistic mobilizations; feminine literature